2016
DOI: 10.1007/s00436-016-5301-1
|View full text |Cite
|
Sign up to set email alerts
|

Myxobolus axelrodi n. sp. (Myxosporea: Myxobolidae) a parasite infecting the brain and retinas of the cardinal tetra Paracheirodon axelrodi (Teleostei: Characidae)

Abstract: An investigation of mortalities in a group of cardinal tetras Paracheirodon axelrodi Meyers, 1936, a popular ornamental fish, revealed myxozoan parasites in ventricles of the brains in 3/10 fish and the ocular retina of a fourth. Parasite impacts were unclear, as additional histopathological findings were present, including bacterial dermatitis and meningitis. Ethanol-preserved specimens pooled from multiple fish were used for morphological characterization of myxospores. Elongate, teardrop myxospores were 20.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Myxobolus freitasi n. sp. has a shape similar to that described for other myxozoans of this genus, such as M. axelrodi, described by Camus et al (2017) infecting Paracheirodon axelrodi, M. toyamai, found in Cyprinus carpio in Japan (Yokoyama & Ogawa, 2015) and M. stellatus infecting Thoracocharax stellatus from Colombia (Stilwell et al, 2020).…”
Section: Discussionsupporting
confidence: 64%
“…Myxobolus freitasi n. sp. has a shape similar to that described for other myxozoans of this genus, such as M. axelrodi, described by Camus et al (2017) infecting Paracheirodon axelrodi, M. toyamai, found in Cyprinus carpio in Japan (Yokoyama & Ogawa, 2015) and M. stellatus infecting Thoracocharax stellatus from Colombia (Stilwell et al, 2020).…”
Section: Discussionsupporting
confidence: 64%
“…(Mitchell, 1989; Cone and Overstreet, 1997; Bahri, 2008; Liu et al ., 2010, 2013, 2014, 2015; Zhang et al ., 2014), including M. bizerti from the gills of M. cephalus , and M. exiguus (misidentified as M. muelleri , as previously mentioned) from the mesenteric vessels of C. ramada (e.g. Longshaw et al ., 2003; Eiras et al ., 2005; Kaur and Singh, 2010; Camus et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(Mitchell, 1989;Cone and Overstreet, 1997;Bahri, 2008;Liu et al, 2010Liu et al, , 2013Liu et al, , 2014Liu et al, , 2015Zhang et al, 2014), including M. bizerti from the gills of M. cephalus, and M. exiguus (misidentified as M. muelleri, as previously mentioned) from the mesenteric vessels of C. ramada (e.g. Longshaw et al, 2003;Kaur and Singh, 2010;Camus et al, 2017). It has been suggested that the origins and radiations of myxosporean parasites probably reflect the evolution of their fish hosts (e.g.…”
Section: Germany Hungarymentioning
confidence: 98%
“…Paracheirodon axelrodi (Schultz); fish imported from Brazil to USA Camus et al (2017) M. balatonicus Székely, Molnár et Cech, 2015 P ellipsoidal, 0.6-0.8 × 0.4-0.4 in gill filaments; SP ellipsoidal in frontal view and lemon-shaped in sutural view, sutural protrusion forming a circular rim around spore, emerging about 0.6 to 1.1 over spore surface, 7 distinct sutural edge marks, 10.1-12.2 × 8.8-10.1 × 7.1-7.8; PC equal, slightly converging anteriorly, 4.9-6 × 3-3.7, NC 6; IP large, cuneiform; GBAN: KP205545. Fig.…”
Section: Discussionmentioning
confidence: 99%